Primordial cosmic fluctuations for variable gravity - Wetterich, Christof (Journal of cosmology and astroparticle physics, 2016)
The observability of primordial cosmic fluctuations does not require a geometric horizon H −1 , which is exceeded temporarily by the wavelength of fluctuations. The primordial information can be protected against later thermal washout even if all relevant wavelengths remain smaller than H −1 . This is demonstrated by formulating the equations governing the cosmic fluctuations in a form that is manifestly invariant under conformal field transformations of the metric. Beyond the field equations this holds for the defining equation for the correlation function, as expressed by the inverse of the second functional derivative of the quantum effective action. An observable almost scale invariant spectrum does not need an expanding geometry. For a variable Planck mass it can even arise in flat Minkowski space.